Space market facing the economic growth in South American countries - Vargas Cuentas, Natalia (2016)
With the recent growth of development in the area of aerospace technology and the new possibilities of starting a small-scale space mission; countries without access to space before, have leapt to the aerospace era and now have access to space in many ways. For example, by carrying out various individual projects or by establishing agreements with other nations, including public or private investment. In that sense, South America, having a significant economic growth in recent times, has become a potential for any company that wants to promote the aerospace technological development in the region. But for this, it is necessary to take into account the implementation of a proper market research and good planning of a strategy to target the problem solving and innovation that Latin American countries need. As will be shown later in this research study, the data indicate that in recent years many South American countries were inclined to invest in remote sensing technology. Considering the above reasons, the present research aims to show the relationship between the economic development of the countries of South America and clear decision to invest in space technology, specifically targeting remote sensing systems.